2017
DOI: 10.1111/exd.13207
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the early local immune response to Ixodes ricinus tick bites in human skin

Abstract: Little is known about the immunomodulation by tick saliva during a natural tick bite in human skin, the site of the tick-host interaction. We examined the expression of chemokines, cytokines, and leukocyte markers on the mRNA levels and histopathologic changes in human skin biopsies of tick bites (n=37) compared to unaffected skin (n=9). Early tick bite skin lesions (<24 h of tick attachment) were characterized by a predominance of macrophages and dendritic cells, elevated mRNA levels of macrophage chemoattrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 31 publications
2
30
0
Order By: Relevance
“…In addition to the tissue breakdown described earlier, the chemotaxis also led to hyperkeratinization, dermal hyperplasia, and oxidative stress involving ROS ( 17 ). Similar findings regarding neutrophil and macrophage chemoattractants were reported in humans bitten by ticks, Ixodes ricinus ( 28 ). Whether basophils, known to secrete histamine and other cytotoxic molecules ( 29 ) also contribute to the inflammatory response in P. leucopus seems unlikely in view of the small numbers found and mostly confined to blood vessels.…”
Section: Discussionsupporting
confidence: 85%
“…In addition to the tissue breakdown described earlier, the chemotaxis also led to hyperkeratinization, dermal hyperplasia, and oxidative stress involving ROS ( 17 ). Similar findings regarding neutrophil and macrophage chemoattractants were reported in humans bitten by ticks, Ixodes ricinus ( 28 ). Whether basophils, known to secrete histamine and other cytotoxic molecules ( 29 ) also contribute to the inflammatory response in P. leucopus seems unlikely in view of the small numbers found and mostly confined to blood vessels.…”
Section: Discussionsupporting
confidence: 85%
“…Numerous studies have shown that several tick salivary factors play differential roles to facilitate evasion of host immune responses (Bowman et al, 1997;Nuttall and Labuda, 2004;Bernard et al, 2015;Kotal et al, 2015;Glatz et al, 2017;Nuttall, 2019). We have shown that tick salivary factors elicit differential levels of fibrinogenolysis upon blood feeding on immunocompetent or immunodeficient mice (Vora et al, 2017).…”
Section: Introductionmentioning
confidence: 84%
“…The same group then showed that tick saliva contains inhibitory activities directed against the chemokines CCL2, CCL3, CCL5, and CCL11 [20]. Importantly, mRNA levels for several of these chemokines are elevated in human skin biopsies from tick bites compared with unaffected skin [21], suggesting that these chemokines are involved in the human reaction to tick bites.…”
Section: Structures Mutationalmentioning
confidence: 95%